2021
DOI: 10.1063/5.0042563
|View full text |Cite
|
Sign up to set email alerts
|

Rapid additive manufacturing of optimized anisotropic metaporous surfaces for broadband absorption

Abstract: Porous materials and metamaterials play a key role in sound absorbing and insulation solutions in acoustics. With the growing interest in additive manufacturing techniques, recent work has focused on the printing of porous and resonant structures for acoustic purposes. Usual metaporous surfaces/interfaces are generally built by periodically inserting resonant elements in an existing porous layer. This complex manufacturing process can be significantly simplified by using additive manufacturing techniques, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In spite of many limitations, additive manufacturing technologies [34] are widely used in recent times to develop and prototype new acoustic materials [35][36][37][38][39][40]. For the specific purposes of this study, the panel samples were additively manufactured from two different raw materials in two technologies: (i) Stereolithography (SLA), a.k.a.…”
Section: Analytical Formulae For Geometry-based Modellingmentioning
confidence: 99%
“…In spite of many limitations, additive manufacturing technologies [34] are widely used in recent times to develop and prototype new acoustic materials [35][36][37][38][39][40]. For the specific purposes of this study, the panel samples were additively manufactured from two different raw materials in two technologies: (i) Stereolithography (SLA), a.k.a.…”
Section: Analytical Formulae For Geometry-based Modellingmentioning
confidence: 99%
“…In practice, it is used to differentiate conventional porous treatments having a weak sub-wavelength behavior, i.e., that cannot reach perfect absorption at normal incidence with h λ/4, from other types of resonator based structures or resonant structures having a strong sub-wavelength behavior, such as treatments based on HRs. Treatments made of porous materials can also achieve sub-wavelength absorption, for instance by incorporating resonant inclusions [25,26,27], optimizing a gradient of properties through their thickness [28,29,30] or folding their structure [31,32,33].…”
Section: Sub-wavelength Folded Qwrsmentioning
confidence: 99%
“…It was demonstrated that the enhancement of sound absorption at frequencies lower than a quarter wavelength results from the Helmholtz resonance in the viscous regime and the trapped modes in the inertial regime. In addition, with the maturity of rapid additive manufacturing technol-ogy, the optimized graded porous materials [34,35], folded metaporous material [36], and anisotropic metaporous surfaces [37] have been fabricated using 3D printing for broadband sound absorption.…”
Section: Introductionmentioning
confidence: 99%